Biochemistry and Health Benefits of Fatty Acids 2018
DOI: 10.5772/intechopen.80429
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Fatty Acids in Human Milk: Benefits and Analysis

Abstract: Human milk is related to the physiological and nutritional welfare of newborns, providing the necessary dietary energy, physiologically active compounds and essential nutrients for breastfed babies. Human milk fat has an important position as energy source, structural and regulatory functions, being one of the most important components of breast milk. It provides approximately 50-60% of the energy of the human milk, and its composition in fatty acids defines its nutritional and physico-chemical properties. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 101 publications
0
13
0
2
Order By: Relevance
“…In addition, TFAs have been associated with adverse effects with respect to essential fatty acid and long-chain PUFA (LCPUFA) metabolism in humans [34], oxidative stress, and infant development [35]. Similar to the previous Ulm birth cohort study [9] and earlier studies [36] in which researchers reported inverse correlations between TFAs and various n-3 and n-6 PUFAs, this fatty acid sub-compositional group comprising TFAs had loadings that are in the opposite direction of the n-3/n-6 dominated sub-compositional group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TFAs have been associated with adverse effects with respect to essential fatty acid and long-chain PUFA (LCPUFA) metabolism in humans [34], oxidative stress, and infant development [35]. Similar to the previous Ulm birth cohort study [9] and earlier studies [36] in which researchers reported inverse correlations between TFAs and various n-3 and n-6 PUFAs, this fatty acid sub-compositional group comprising TFAs had loadings that are in the opposite direction of the n-3/n-6 dominated sub-compositional group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, the intake of milk and calcium [21] was far below the recommendations [26]. We showed that the intake of milk and dairy products was positively associated with SFAs in HM and negatively associated with HM MUFAs, n-6 PUFAs, LA and EPA, that is, mostly associated with changes toward a less healthy HM FA composition [38]. Meat/poultry and eggs were other foods that were negatively associated with n-6 PUFAs, LA, and/or EPA in HM.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that bacterial inoculants did not grow in the reconstituted irradiated FD-DHM powder due to the minimal impact of freeze-drying [ 40 ] and gamma-irradiation on the bile-salt-stimulated lipase activity and, hence, its preservation in the reconstituted samples [ 43 ]. Lipase increases lipid hydrolysis, thus increasing free fatty acids and monoglycerides, both known to have strong antimicrobial properties [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. More recently, we have found an elevated level of free fatty acids in the volatiles of irradiated samples compared to raw and Holder-pasteurised DHM (unpublished data).…”
Section: Discussionmentioning
confidence: 99%